Kebijakan Pengelolaan Lingkungan Di Kabupaten Tulungagung dan Peranan Masyarakat Dalam Melestarikan Lingkungan - Artha Yoma Nendra Yakthi; Faisal Maulana Putra; Fitri Choirun Nisa; Rizka Fikri Nabilah; Hany Nurpratiwi (Concept: Journal of Social Humanities and Education, 2023)
The aims of this research are 1. to find out environmental management policies in Indonesia in general; 2. know the environmental management policies in Tulungagung Regency; 3. knowing environmental problems in Tulungagung Regency; and 4. knowing the role of the community in maintaining, protecting, and preserving the environment. This study uses a qualitative approach to content analysis, using the literature study method. Sources of data used, namely articles, journals, research reports, and other sources that have a good reputation. The results of this study indicate that environmental problems in Tulungagung Regency are increasing pollution and increasing the volume of waste. Apart from referring to Law Number 32 of 2009, the local government also has a regional regulation, namely the Tulungagung Regency Regional Regulation Number 14 of 2018 concerning Environmental Protection and Management. The Tulungagung Regency environmental management strategy focuses on environmental functions, especially controlling environmental impacts by preventing, restoring environmental damage and pollution in the framework of achieving environmental goals of sustainable and environmentally sound regional development.